Watan - Omar Nidal Raddad; Layan Najeh Otman (My University, 2025)
This project is about a social media application that has been developed for helping Palestinians deal with the day-to-day challenges that they face while living under occupation. The application does not simply connect people but enables users to deal with the challenges of distance, barriers and checkpoints that make travel a real nightmare. Featuring built in maps, it offers users the shortest and safest routes hence enabling them to move around faster with less trouble. Also important is the market community section of the application, which allows users to post and browse advertisements for goods and services to be purchased or offered within the community, enhancing the economic activity as well as community bonding. Incorporating technology into every day realities of Palestinians, this app is not only aimed at socializing, but socializing with the aim of improving one’s life, creating and enhancing relationships and possibilities which are quite in their scarcity. There is an element in this project which indicates how technology may engage its users to socialize and also ease their experience in an environment that is difficult.